Novel Solid Electrolytes for Li-Ion Batteries: A Perspective from Electron Microscopy Studies - Ma, Cheng; Chi, Miaofang (Frontiers in Energy Research, 2016)
Solid electrolytes can simultaneously overcome two of the most formidable challenges of Li-ion batteries: the severe safety issues and insufficient energy densities. However, before they can be implemented in actual batteries, the ionic conductivity needs to be improved and the interface with electrodes must be optimized. The prerequisite for addressing these issues is a thorough understanding of the material’s behavior at the microscopic and/or the atomic level. (Scanning) transmission electron microscopy is a powerful tool for this purpose, as it can reach an ultrahigh spatial resolution. Here, we review recent electron microscopy investigations on the ion transport behavior in solid electrolytes and their interfaces. Specifically, three aspects will be highlighted: the influence of grain interior atomic configuration on ionic conductivity, the contribution of grain boundaries, and the behavior of solid electrolyte/electrode interfaces. Based on this, the perspectives for future research will be discussed.